The econometric analysis of seasonal time series - Ghysels, Eric, 1956-; Osborn, Denise R. (New York : Cambridge University Press, 2001)
Provides a thorough and timely review of the recent developments in the econometric analysis of seasonal economic time series, summarizing a decade of theoretical advances in the area. The authors discuss the asymptotic distribution theory for linear stationary and nonstationary seasonal stochastic processes.
Includes bibliographical references (p. 207-221) and indexes.
oif 05/05/15
Loan
Keywords: Time-series analysis; Econometrics